2022
DOI: 10.3390/electronics11020185
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting Selfish Nodes Using Reputation Based System in Mobile Ad Hoc Networks

Abstract: A mobile ad hoc network (MANET) is a group of nodes constituting a network of mobile nodes without predefined and pre-established architecture where mobile nodes can communicate without any dedicated access points or base stations. In MANETs, a node may act as a host as well as a router. Nodes in the network can send and receive packets through intermediate nodes. However, the existence of malicious and selfish nodes in MANETs severely degrades network performance. The identification of such nodes in the netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Tis also overcomes the overftting problem and results in higher accuracy. In order to improve accuracy and to come up with a novel approach as compared to the existing work, we have implemented the proposed hybrid model with the best combination of GB, GNB, and decision tree, along with the random forest classifers [24][25][26][27]. Te results described in Table 6 show that diagnosis of chronic kidney disease is efective using the random forest with combination as a stacking technique in the hybrid model.…”
Section: Resultsmentioning
confidence: 99%
“…Tis also overcomes the overftting problem and results in higher accuracy. In order to improve accuracy and to come up with a novel approach as compared to the existing work, we have implemented the proposed hybrid model with the best combination of GB, GNB, and decision tree, along with the random forest classifers [24][25][26][27]. Te results described in Table 6 show that diagnosis of chronic kidney disease is efective using the random forest with combination as a stacking technique in the hybrid model.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, some recent studies are given below. Fayaz et al 29 suggested a reputation-based model for predicting selfish nodes and enforcing cooperation through the analysis of contribution and consumption data. To safeguard resources with a positive reputation, non-cooperative nodes are excluded from the network.…”
Section: State-of-the-art Workmentioning
confidence: 99%
“…At the end of the simulation, the hop count for the proposed RHCC-DAODV protocol decreased by nearly 94 depending on the varying number of selfish nodes. Table 3 presents performance metrics for different routing protocols, including Reputation-based scheme, 29 AISBA, 30 Chimp-CoCoWa-AODV, 31 BTRP, 32 ANFIS-EESC, 33 and RHCC-DAODV (proposed). PDR is the percentage of packets sent that successfully reached their intended destinations.…”
Section: F I G U R E 12 Analysis Of Packet Drop Ratiomentioning
confidence: 99%
“…Fayaz et al 22 have proposed a reputation‐based mechanism that uses consumption to contribution (C2C) information for identifying selfish nodes and enforcing cooperation. Nodes that do not cooperate are removed from network to conserve resources of nodes with better standing.…”
Section: Related Workmentioning
confidence: 99%